2020
DOI: 10.3390/vaccines8020275
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Analysis of the Hepatitis B Virus “a” Determinant Displayed on Chimeric Virus-Like Particles of Macrobrachium rosenbergii Nodavirus Capsid Protein Produced in Sf9 Cells

Abstract: Chimeric virus-like particles (VLPs) have been widely exploited for various purposes including their use as vaccine candidates, particularly due to their ability to induce stronger immune responses than VLPs consisting of single viral proteins. In the present study, VLPs of the Macrobrachium rosenbergii nodavirus (MrNV) capsid protein (Nc) displaying the hepatitis B virus “a” determinant (aD) were produced in Spodoptera frugiperda (Sf9) insect cells. BALB/c mice immunised with the purified chimeric Nc-aD VLPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 56 publications
4
14
1
Order By: Relevance
“…The heterogeneous population of VLPs analysed via DLS showed that most of them (13.1%) were ~43.8 in diameter. However, the size of Nc-aD-Sf9 VLPs as observed by TEM was ~38 ± 17 nm [19], which is smaller than that determined by DLS analysis. The size difference could be due to the fact that DLS measures the size of particles in solution, and TEM involves size measurement of dried particles [29].…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…The heterogeneous population of VLPs analysed via DLS showed that most of them (13.1%) were ~43.8 in diameter. However, the size of Nc-aD-Sf9 VLPs as observed by TEM was ~38 ± 17 nm [19], which is smaller than that determined by DLS analysis. The size difference could be due to the fact that DLS measures the size of particles in solution, and TEM involves size measurement of dried particles [29].…”
Section: Discussioncontrasting
confidence: 60%
“…ELISA revealed that the sera from these immunised mice recognised the aD epitope of HBV. Furthermore, we demonstrated that Nc-aD-Sf9 VLPs significantly induced the increase in NK cell, CTL and memory B cell populations [19]. In the present study, the cytokine profile elicited by Nc-aD-Sf9 VLPs suggests that the vaccine candidate could mediate HBV clearance by Th1-and Th2-regulated T-cell responses.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations